Faktor Kecenderungan Lingkungan Penyalahguna Narkoba (Studi Kasus Alasan Pelaku Penyalahguna Narkoba Dalam Konteks Komunikasi Antar Pribadi di Jakarta) - Nurlina Rahman (Proceedings of The ICECRS, 2019)
The aim of this research is to find the reason for the user of substance abuse by understanding environment factor as one of tendency factors. Research method was a qualitative. The research subject was 16 people that majority were age of 10 – 16 years old when started using drugs (1 person started using drugs in primary school). Sampling techniques were snow-ball sampling. The result showed that someone will be onvolved in substance abuse until addicted phase if there was tendency factor. The tendency factor was environment factor that can be a trigger of substance abuse. Therefore, this research was expected to give understanding in society especially environment and educational authorityto aware the early symptoms of substance abuse. This case has been a concern of social phenomenon because drug trafficking